2017
DOI: 10.1016/j.jamda.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A U-shaped Association Between Blood Pressure and Cognitive Impairment in Chinese Elderly

Abstract: Objectives Higher or lower blood pressure may relate to cognitive impairment, while the relationship between blood pressure and cognitive impairment among the elderly is not well-studied. The study objective was to determine whether blood pressure is associated with cognitive impairment in the elderly, and, if so, to accurately describe the association. Design Cross-sectional data from the sixth wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) conducted in 2011 Setting Community-based sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 50 publications
4
29
4
Order By: Relevance
“…H ypertension guidelines recommend lowering systolic blood pressure (SBP) in older patients, but cohort studies have raised concern that lowering SBP too much might harm these patients by, for example, accelerating cognitive decline. [1][2][3][4][5][6][7][8][9][10][11] A recent network metaanalysis of 17 hypertension trials proved the effectiveness and safety of lowering SBP to <130 mm Hg in patients with hypertension, 12 spurring the American College of Cardiology/American Heart Association to update their guidelines to recommend lowering SBP to <130 mm Hg for noninstitutionalized older patients. 13 Hypertension trials, however, often exclude older, frail patients and those with complex health problems, 14 and many have questioned the generalizability and applicability of the results of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…H ypertension guidelines recommend lowering systolic blood pressure (SBP) in older patients, but cohort studies have raised concern that lowering SBP too much might harm these patients by, for example, accelerating cognitive decline. [1][2][3][4][5][6][7][8][9][10][11] A recent network metaanalysis of 17 hypertension trials proved the effectiveness and safety of lowering SBP to <130 mm Hg in patients with hypertension, 12 spurring the American College of Cardiology/American Heart Association to update their guidelines to recommend lowering SBP to <130 mm Hg for noninstitutionalized older patients. 13 Hypertension trials, however, often exclude older, frail patients and those with complex health problems, 14 and many have questioned the generalizability and applicability of the results of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other longitudinal studies have shown an association between reduced cognitive function on processing speed and verbal memory and elevated BP in midlife, defined as a systolic BP (SBP) of 120‐139 mm Hg and diastolic blood pressure (DBP) of 80‐89 mm Hg . However, a few other studies reported either no association or a U‐shaped association, which is an elevated risk at lower and higher BP, between hypertension in midlife and cognition in late life …”
Section: The Evidence From Observational Studiesmentioning
confidence: 99%
“…The evidence in several studies is mixed, including results that show a significant association between high BP and worsening cognitive function, no association, a U‐shaped association, or even the opposite association . One large study—the Framingham Heart Study—also reported no significant association between late‐life BP and cognitive function …”
Section: The Evidence From Observational Studiesmentioning
confidence: 99%
“…Studies in Asia have shown that hypertension is associated with incidence of dementia in the elderly . Indeed, not only is hypertension directly related to cognitive function, but hypertension that occurs in midlife (around the age of 45‐55 years) also affects the incidence of cognitive impairments in later life .…”
Section: Midlife Hypertension and Cognitive Impairmentmentioning
confidence: 99%
“…Studies in Asia have shown that hypertension is associated with incidence of dementia in the elderly. [65][66][67][68][69] Indeed, not only is hypertension directly related to cognitive function, but hypertension that occurs in midlife (around the age of 45-55 years) also affects the incidence of cognitive impairments in later life. 46,70,71 An analysis conducted in conjunction with the Hisayama study, a prospective cohort study in Japan performed over 32 years (1973-2005), was designed to compare blood pressure in midlife and late life, and to compare these data with dementia output and its subtypes.…”
Section: Midlife Hyperten S I On and Cog Nitive Impairmentmentioning
confidence: 99%